Religious-Based Organizations (RBOs) as Non-State Actors in Peacebuilding and Regional Governance in Southeast Asia - Qudsi Mutawakil Husaini (Pen of Social Science, 2026)
This article examines the role of Religious-Based Organizations (RBOs) as non-state actors in peacebuilding and regional governance in Southeast Asia. The study addresses the increasing relevance of religion in International Relations (IR), particularly in a region characterized by religious diversity and recurring ethno-religious conflicts. Using a qualitative literature-based approach, this article analyzes the activities of major RBOs in Indonesia and the Philippines, including Nahdlatul Ulama (NU), Muhammadiyah, and the Bishops-Ulama Conference (BUC). The analysis employs Constructivist and Liberal perspectives to explain how RBOs contribute to norm diffusion, interfaith dialogue, conflict mediation, and humanitarian diplomacy. The findings show that RBOs possess moral legitimacy, grassroots networks, and transnational connections that enable them to influence peacebuilding processes beyond formal state mechanisms. However, their effectiveness remains constrained by weak state collaboration, bureaucratic exclusion, political instrumentalization of religion, and internal ideological fragmentation. The article argues that RBOs function as strategic actors in promoting social cohesion and regional stability in Southeast Asia, although their long-term contribution depends on institutional recognition and stronger multi-level cooperation between religious organizations, civil society, and state actors.